Nesting Activity and Behavior of Osmia cornifrons (Hymenoptera: Megachilidae) Elucidated Using Videography - Matthew I. McKinney; Yong-Lak Park (Psyche: A Journal of Entomology)
Osmia cornifrons Radoszkowski (Hymenoptera: Megachilidae) is utilized as an alternate pollinator to Apis mellifera L. (Hymenoptera: Apidae) in early-season fruit crops. This study was conducted to investigate nesting activities and associated behaviors of O. cornifrons. Osmia cornifrons nesting activity was recorded by using a digital video recorder with infrared cameras. Nesting behavior of ten female O. cornifrons was observed, and the number of nesting trips per hour was recorded. Trends in daily activity were determined with regression analysis, and chi square analysis was used to determine if O. cornifrons spent a greater amount of time performing certain activities. The percentage of time required to gather nesting resources and complete nest construction activities was recorded from the video footage. Results of this study showed that pollen gathering was the most time-consuming gathering activity, requiring 221.6±28.69 min per cell and cell provisioning was the most time-consuming intranest activity, requiring 28.9 min ± 3.97 min. We also found that O. cornifrons activity was correlated with time of day, temperature, and precipitation. Various nesting behaviors, including cell provisioning and partitioning, oviposition, grooming, resting and sleeping, nest-searching, and repairing behaviors, are described in this paper.